2014
DOI: 10.1080/15459624.2014.895372
|View full text |Cite
|
Sign up to set email alerts
|

Exposures and Cross-shift Lung Function Declines in Wildland Firefighters

Abstract: Respiratory problems are common among wildland firefighters. However, there are few studies directly linking occupational exposures to respiratory effects in this population. Our objective was to characterize wildland fire fighting occupational exposures and assess their associations with cross-shift changes in lung function. We studied 17 members of the Alpine Interagency Hotshot Crew with environmental sampling and pulmonary function testing during a large wildfire. We characterized particles by examining si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
1
43
4
Order By: Relevance
“…Although a number of studies have examined short‐term and cross‐seasonal effects of wildland firefighting, the results reported in this cross‐sectional study are the first to shed light on the potential health consequences of longer durations of wildland firefighting experience. Most studies of WLFF health have emphasized respiratory effects [Betchley et al, , Gaughan et al, , ]. In the relatively young population included here, the prevalence of most self‐reported measures of chronic respiratory illness (e.g., chronic obstructive pulmonary disease) was extremely low.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although a number of studies have examined short‐term and cross‐seasonal effects of wildland firefighting, the results reported in this cross‐sectional study are the first to shed light on the potential health consequences of longer durations of wildland firefighting experience. Most studies of WLFF health have emphasized respiratory effects [Betchley et al, , Gaughan et al, , ]. In the relatively young population included here, the prevalence of most self‐reported measures of chronic respiratory illness (e.g., chronic obstructive pulmonary disease) was extremely low.…”
Section: Discussionmentioning
confidence: 85%
“…It is critical to understand how these exposures affect long‐term health. Wildland firefighters (WLFFs) are exposed to numerous air pollutants including particulate matter (PM) [Gaughan et al, ], nitrogen oxides [Naeher et al, ], benzene [Booze et al, ], carbon monoxide [Adetona et al, ], silica [Harrison et al, ], and polycyclic aromatic hydrocarbons (PAHs) [Adetona et al, ]. Although the long‐term risks to health associated with occupational exposure to wildland fire events are not well‐characterized, each of these pollutants has known long‐term health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of levoglucosan, a sugar anhydride by-product of incomplete combustion of cellulose, may be used to indicate relative exposure to products of pyrolysis from burning biomass [Simoneit et al, 1999]. A recent study examined personable exposure to airborne respirable levoglucosan using a Dorr-Oliver cyclone and air sampling pump, and cross-shift changes in lung function in a population of 17 wildland firefighters for 4 days at a large wildland fire [Gaughan et al, 2014]. The authors reported that levoglucosan was found mainly in the respirable fraction, defined as under 2.5 μm, with higher concentrations during fireline construction than in mop-up operations.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from CO, wildfire smoke contains particulates of 2.5 microns in diameter, polyaromatic hydrocarbons, and levoglucosan, a product of combustion of cellulose. Several studies have shown that these products of wood combustion may decrease lung function in wildland fire fighters across fire seasons [Adetona et al 2013;Gaughan et al 2014;Hagberg et al 1985;Harrison et al 1995]. The extent to which of these specific factors may impact lung function may vary between individuals.…”
Section: Wood Dustmentioning
confidence: 99%